Rosa Barba: solo exhibition at MAXXI - Barba, Rosa (MAXXI | Museo nazionale delle arti del XXI secolo, 2025)
A mid career retrospective exhibition celebrating the work of artist and filmmaker Rosa Barba, whose practice destabilses the conceptual terms of cinematic space.